2012
DOI: 10.1080/1359432x.2012.713550
|View full text |Cite
|
Sign up to set email alerts
|

The role of irritability in the relation between job stressors, emotional reactivity, and counterproductive work behaviour

Abstract: Researchers have stressed the importance of assessing individual differences in personality as an approach to understanding aggressive and deviant conduct across different contexts. This study investigated the moderation role of irritability, a specific aggression-related disposition, in the process of work stressors that are conducive to counterproductive work behavior (CWB) within the stressor-emotion model. From a total sample of 1,147 Italian workers (53.5% women), high-and low-irritability groups were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 88 publications
3
28
0
Order By: Relevance
“…Thus, it pinpoints an unexplored, indirect, harmful role of employees' deviant personality traits; they can serve as catalysts that stimulate the conversion of time-related work stress into enhanced CWB. With this focus on the invigorating role of the dark triad, which is aberrant, socially malevolent, and destructive (Paulhus and Williams, 2002;Smith and Lilienfeld, 2013), this study also extends research that notes how other, less extreme individual factors, such as a lack of agreeableness (Skarlicki et al, 1999), irritability (Fida et al, 2014), or negative affectivity (Penney and Spector, 2005), moderate the effect of adverse work conditions on negative work behaviours.…”
Section: Contributionssupporting
confidence: 56%
See 1 more Smart Citation
“…Thus, it pinpoints an unexplored, indirect, harmful role of employees' deviant personality traits; they can serve as catalysts that stimulate the conversion of time-related work stress into enhanced CWB. With this focus on the invigorating role of the dark triad, which is aberrant, socially malevolent, and destructive (Paulhus and Williams, 2002;Smith and Lilienfeld, 2013), this study also extends research that notes how other, less extreme individual factors, such as a lack of agreeableness (Skarlicki et al, 1999), irritability (Fida et al, 2014), or negative affectivity (Penney and Spector, 2005), moderate the effect of adverse work conditions on negative work behaviours.…”
Section: Contributionssupporting
confidence: 56%
“…Notably, the influences of these contextual and individual factors cannot be seen in isolation; the extent to which exposure to adverse work conditions may escalate into negative work behaviours is greater, for example, among employees who score high on negative affectivity (Skarlicki et al, 1999) and irritability (Fida et al, 2014) or low on emotional intelligence (Greenidge and Coyne, 2014), agreeableness (Skarlicki et al, 1999), and honesty-humility (Chirumbolo, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Irritability at home or work can have negative consequences . Irritability was found to impair accurate recognition of affect in others, to decrease social cognition or mentalizing, as well as mutual affection in relationships, and to exacerbate interpersonal stress .…”
Section: Discussionmentioning
confidence: 99%
“…Family, friends, and work colleagues commonly find it difficult to know how to respond when interacting with a person who is irritable . Ensuing interpersonal stress and high expressed emotion can increase the risk of affective relapse, and undermine relationships and job security …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other research has found that organizational aspects, such as the lack of social support, injustices, role ambiguity, and role conflict, can play a relevant role in the development of CWB [16]. In addition, previous studies have investigated the relationship between personal characteristics [17][18][19] and certain demographic factors [20] or even organizational factors [21,22].…”
Section: Cwb Has Been Categorized Into Actions Directed Toward Organimentioning
confidence: 99%